2004
DOI: 10.1097/01.alc.0000148115.90045.c5
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Is a Cofactor for Malondialdehyde‐Acetaldehyde Adduct–Mediated Cytokine/Chemokine Release by Rat Sinusoidal Liver Endothelial and Kupffer Cells

Abstract: These studies strongly suggest that the sensitization of SECs and KCs by LPS plays a significant role in the development and/or progression of alcoholic liver disease, and the subsequent activation by MAA-modified proteins may be a mechanism by which proinflammatory processes are initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 45 publications
2
52
0
Order By: Relevance
“…Sinusoidal liver endothelial cells were prepared by perfusion and differential centrifugation methods as described previously (Braet et al, 1994;Duryee et al, 2004). Cell number and viability was determined by trypan blue exclusion and counting on a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…Sinusoidal liver endothelial cells were prepared by perfusion and differential centrifugation methods as described previously (Braet et al, 1994;Duryee et al, 2004). Cell number and viability was determined by trypan blue exclusion and counting on a hemocytometer.…”
Section: Methodsmentioning
confidence: 99%
“…This is consistent with the idea that adaptation is induced by chronic EtOH exposure. It should also be noted that effects of chronic EtOH exposure on the immune system can be relatively persistent, and mechanisms such as increased production of reactive oxygen species and cellular damage caused by the reactive EtOH metabolite acetaldehyde have been implicated in chronic effects of EtOH on the immune system (32,33). In addition, the effects of acute EtOH exposure on lipid rafts discussed later in this review are relatively short-lived.…”
Section: Lipid Rafts and Alcoholmentioning
confidence: 99%
“…Previous studies in our laboratory have shown the induction by MAA-adducts of pro-inflammatory cytokines/chemokines and adhesion molecules [13,15]. An increase in fibronectin secretion by SECs of the liver in response to MAA-adduct stimulation may be one method by which chronic alcohol consumption induces fibrosis leading to cirrhosis.…”
Section: Discussionmentioning
confidence: 85%
“…Briefly, following isolation cells were counted on a hemocytometer and the viability was determined by trypan blue exclusion, and found to be greater than 85% viable. SEC purity was assessed by staining with antibodies specific for the various cell types of the liver using a Fluorescent Activated Cell Scanner (FACSCalibur, San Jose, CA) as previously reported [13]. SECs were determined to be >90% pure.…”
Section: Isolation Of Liver Sinusoidal Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation